The structural, metamorphic and magmatic evolution of the Greater Himalayan Sequence and Main Central Thrust, Eastern Nepal Himalaya - Streule, M (2009)
Field observations of the Greater Himalayan Sequence in Eastern Nepal demonstrate a ductile, highly strained package of metamorphic rocks that show extensive evidence of crustal anatexis throughout. These can be distinguished from the Lesser Himalayan sequence below by a distinct reduction in metamorphic grade, an inverted metamorphic sequence and a high strain zone corresponding to the Main Central Thrust. Metamorphic studies are combined with geochronology to demonstrate a protracted period of crustal melting followed by rapid decompression from 18.7 Ma to 15.6 Ma. A metamorphic decompression rate is quantified at c.2mm/yr during this period. This is interpreted to represent exhumation of the Greater Himalayan Sequence by a process of ductile, channelised flow from the mid-crust beneath Tibet. Below a prominent band of kyanite gneiss, previously used to locate the Main Central Thrust, but here mapped within the Greater Himalayan Sequence, partial melting is still exhibited. Here monazites are dated at 10.6 Ma. In the Lesser Himalaya below, allanites record a similar 10.1 Ma event. This implies that following channel flow during the mid-Miocene, the channel widened in the lower-Miocene to incorporate a greater structural thickness. Following these two periods of exhumation and ductile extrusion, separated in time and space, Fission Track studies indicate that much slower, erosion driven exhumation proceeded, at <1 mm/yr. This rate increases slightly in the Pliocene, most likely in response to Northern Hemisphere glaciation; no difference in exhumation is seen across the Greater Himalayan Sequence with respect to the different, earlier, phases of ductile channel flow related exhumation. These results demonstrate the episodic nature of channel flow in the Himalaya and reconcile arguments about the position of the MCT in Eastern Nepal.